Pengaruh Motivasi Kerja dan Kepemimpinan terhadap Kinerja Karyawan - Mudjiran Mudjiran; Siti Noor Hidayati (Universitas Proklamasi 45 Yogyakarta, 2013)
Performance is the work result of the employees to achieve of some company goals. The purpose of this researches is to determine the effect of leadership and work motivation to the employee performance as partial and simultaneous at the UPT Pasar I Kabupaten Sleman. Research using multiple regression analysis. The result showed leadership and work motivation a significant positive effect on employee performance. It was also concluded thatleadership variable dominanly influenced on employee performance compared to work motivation.